2015
DOI: 10.1016/j.neulet.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paired transcutaneous electrical stimulation delivered at single and dual sites over lumbosacral spinal cord

Abstract: It was demonstrated previously that transcutaneous electrical stimulation of multiple sites over the spinal cord is more effective in inducing robust locomotor behavior as compared to the stimulation of single sites alone in both animal and human models. To explore the effects and mechanisms of interactions during multi-site spinal cord stimulation we delivered transcutaneous electrical stimulation to the single or dual locations over the spinal cord corresponding to approximately L2 and S1 segments. Spinally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 27 publications
(35 reference statements)
2
36
0
1
Order By: Relevance
“…Intrathecal electric stimulation of afferents and particularly the dorsal columns or peripheral stimulation have been shown to promote locomotor activity or facilitate other movements (19,88,89,241,243,330,404,405,462). Currently, this approach seems to be the most promising way to elevate the excitability in the spinal cord networks of spinal cord injury patients to a degree so that the remaining brain stem fibers from LGPi can initiate the locomotor activity, particularly if combined with locomotor training.…”
Section: Spinal Cord Injury: Brief Commentmentioning
confidence: 99%
“…Intrathecal electric stimulation of afferents and particularly the dorsal columns or peripheral stimulation have been shown to promote locomotor activity or facilitate other movements (19,88,89,241,243,330,404,405,462). Currently, this approach seems to be the most promising way to elevate the excitability in the spinal cord networks of spinal cord injury patients to a degree so that the remaining brain stem fibers from LGPi can initiate the locomotor activity, particularly if combined with locomotor training.…”
Section: Spinal Cord Injury: Brief Commentmentioning
confidence: 99%
“…In these preparations, electrical stimulation with stereotyped trains of square impulses triggered brief episodes of electrical oscillations, alternating between flexor and extensor motor pools on both sides of the cord (fictive locomotion rhythm, FL; [25]), when selectively delivered through tight fitting electrodes to either DRs [147] or sacrocaudal afferents [148]. In addition, activation of multiple DRs with staggered pulses [149,150] effectively generated FL, indicating a multi-segmental convergence of afferent inputs on neuronal circuits during electrical spinal cord stimulation, as also reported in both in vivo animals [151] and in humans [100,152].…”
Section: Selective Electrostimulation Of Dorsal Roots Triggers Locomomentioning
confidence: 53%
“…Previous studies have shown that improved locomotor performance is closely associated with improved coordination of motor pools [5]. TSCS at T11 and L1 vertebral levels of proximal and distal motor pools in paralyzed subjects are facilitated [24]. This effect is evident in spinal motor evoked potentials of proximal and distal leg muscles to single stimulation pulses [23].…”
Section: Discussionmentioning
confidence: 93%